Insight into Nrf2: a bibliometric and visual analysis from 2000 to 2022 - Ma, Yawei; Wang, Zhongqing; Hu, Yuedong (Frontiers in Genetics, 2023)
Background: Nrf2 plays a pivotal role in governing the antioxidant defense system, triggering the transcription of diverse genes involved in cellular protection. Its role in mitigating oxidative damage and modulating inflammatory processes has made Nrf2 an attractive target for therapeutic interventions. Despite the growing interest in Nrf2 research, a bibliometric analysis is relatively rare. This study aimed to clarify Nrf2's role in multiple diseases, identify emerging trends and hotspots using bibliometric analysis, and provide valuable insights and potential directions for future therapeutic interventions.